Management of stemborer Busseola fusca (Lepidoptera: Noctuidae) using sowing date, host plant and chemical control in sorghum in the highlands of Eritrea. (25th March 2015) - Haile, Adugna
Abstract : The effects of sowing date, host plant and insecticidal control of the stemborer Busseola fusca Fuller were studied in the highlands of Eritrea at Halhal Begos in 2003–2005. Sowing date had a significant effect on stemborer incidence and damage levels. Early sowing dates (April 1 and 15) had significantly lower numbers of larvae, percent infestation and deadhearts, and produced higher yields compared with later sowing dates. In the host preference experiment, Sudangrass ( Sorghum × drummondii (Steud.) Millsp. & Chase) had the highest infestation (91%), and it was the most preferred host for oviposition among the tested plants. All the chemical treatments significantly reduced stemborer infestation and damage levels compared with untreated plots. Furadan and Cymbush significantly lowered infestation and larval damage. There were significant differences in days to heading, maturity, plant height and yield. In general, the study showed that early planting coupled with host preference and insecticides reduced the infestation of stemborers and significantly increased the yield of sorghum in the highlands of Eritrea.